Properties of limestone Mollic leptosols in the "Mrkonjićko" forest management area - Ilija Čigoja; Marijana Kapović Solomun; Saša Eremija; Goran Česljar (Glasnik Šumarskog Fakulteta Univerziteta u Banjoj Luci)
The paper describes the physical and chemical properties of limestone Mollic leptosols, as one of the most common soil types in the forest management area "Mrkonjićko". Research was carried out in two forest management units (FMU): "Dubička gora" in compartment 60 and "Ovčara", in compartments 18 and 64. The „Mrkonjićko“ forest management area is located in the southwestern part of the Republic of Srpska, under the influence of a mountain climate. The research aims to study the physical and chemical properties of limestone Mollic leptosols in different environmental conditions and define their ecological production potential. Three soil profiles were opened, and soil samples were taken from genetic horizons. The laboratory analysis included investigations of the soil's standard physical and chemical properties. The total depth of the analyzed profiles ranges from 16 to 20 cm. The textural class is loam, while the soil reaction in H2O is neutral. Analyzed soils are poor in available phosphorus, and the supply of K2O ranges from medium to good. The physical and chemical properties of the investigated soil profiles are generally favorable for the growth and development of vegetation. However, the depth of this soil type is a limiting factor in its productivity.